Predation by Insidious Flower Bug, Orius insidiosus, Adults on Western Flower Thrips, Frankliniella occidentalis, Adults under Laboratory and Greenhouse Conditions - Conner, Mary A.; Herrick, Nathan J.; Cloyd, Raymond A. (My University, 2017)
Western flower thrips, Frankliniella occidentalis (Perg.), is a major insect pest of greenhouse production systems. A widely-used plant protection strategy is biological control, which entails releasing natural enemies; such as parasitoids and predators, that are commercially available from suppliers or distributors. Studies to assess predation of predatory mites and predatory bugs against specific prey are typically conducted under laboratory conditions. However, results obtained under laboratory conditions may not be equivalent to results observed under field conditions; including greenhouses when plants are present. Therefore, the goal of our study was to compare predation by insidious flower bug, Orius insidiosus Say, adults under laboratory and greenhouse conditions to determine if flower morphology of transvaal daisy, Gerbera jamesonii, cut flowers affects predation by adult insidious flower bugs on western flower thrips adults.